The Effects of Hyperbaric Oxygen and Active Recovery on Lactate Removal and Fatigue Index - Widiyanto; Soetanto Hartono (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
The purpose of this study was to compare active recovery and recovery using hyperbaric oxygen on lactate removal and fatigue index. Fatigue index was measured through Running-based Anaerobic Sprint Test (RAST). Lactate clearance was measured using lactate analyzer. Recovery period is important since competitive events are sometimes very close one from the other.The design of this research was randomized pretest posttest control group design. Thirty students were randomly assigned to three groups consisted of 10 students, the fi rst group doing recovery using 1.3 ATA hyperbaric oxygen after doing RAST, the second group doing recovery in 1.8 ATA hyperbaric oxygenafter doing RAST, and the third group doing active recovery with light intensity after doing RAST. Blood lactate concentration was measured before RAST, ten minutes after RAST, and after recovery either using hyperbaric oxygen or active recovery, and then they took RAST again to get the second fatigue index. Data was analyzed through Manova with .05 signifi cant levels. Blood lactate level isthe lowest in those treated with Hyperbaric Oxygen 1.3 ATA has signifi cant diff erence with active recovery (p=.008). Fatigue index of those treated with hyperbaric oxygen 1.3 ATA is the lowest (6.7 watts/second) vs HBO 1.8 ATA (7.85 watts/second) and active recovery (8.56 watts/second). Increasing oxygen supply to musculoskeletal system increases metabolism of waste substances and promotes recovery from fatigue. Hiperbaric Oxygen 1.3 ATA is more eff ective than HBO 1.8 ATA or active recovery in lactate removal.